The role of the Src Homology-2 domain containing protein B (SHB) in β cells. (20th October 2015) - Welsh, Michael; Jamalpour, Maria; Zang, Guangxiang; Åkerblom, Björn
Abstract : This review will describe the SH2-domain signaling protein Src Homology-2 domain containing protein B (SHB) and its role in various physiological processes relating in particular to glucose homeostasis and β cell function. SHB operates downstream of several tyrosine kinase receptors and assembles signaling complexes in response to receptor activation by interacting with other signaling proteins via its other domains (proline-rich, phosphotyrosine-binding and tyrosine-phosphorylation sites). The subsequent responses are context-dependent. Absence of Shb in mice has been found to exert effects on hematopoiesis, angiogenesis and glucose metabolism. Specifically, first-phase insulin secretion in response to glucose was impaired and this effect was related to altered characteristics of focal adhesion kinase activation modulating signaling through Akt, ERK, β catenin and cAMP. It is believed that SHB plays a role in integrating adaptive responses to various stimuli by simultaneously modulating cellular responses in different cell-types, thus playing a role in maintaining physiological homeostasis.